SOCIALIZATION OF LONG TERM CONTRACEPTION FAMILY PLANNING PROGRAM BKKBN SIDOMULYO LAMPUNG SELATAN - Evadianti, Yuli; Sahriyani, Retno Suhesi (Journal of Public Relations and Digital Communication (JPRDC), 2024)
. Contraception Period Long that is is method usage contraception futures long Which in its use have effectiveness And level continuity usage Which tall with number failure Which low. The classification contraception period long consists from tool contraception IUD, Implant, And Contact (steady contraception). To inform how to use contraception In the long term, the instructor's skills as a communicator are needed, as well notice message What just Which will be delivered as well as media What Which will used as an important point for the success of the implementation of socialization, apart from that it is also necessary Pay attention to behavior and character society will get it socialization about contraception period long program Family Planned. Question research in writing this thesis is what is the implementation of socialization like? carried out by officers instructor contraception period long family program planned BKKBN Sidomulyo South Lampung and anything else obstacles faced by officers counselors in implementing long-term contraceptive socialization for family programs planning BKKBN Sidomulyo South Lampung. The method used is method qualitative description with two person key informant as well as nine person informant. The conclusion in this research is the implementation of socialization carried out by officers long-term contraceptive instructor for the BKKBN Sidomulyo family planning program Lampung South form team executor until activity in the field, with prepare materials and props when carrying out socialization, and carry out personal approach and come to residents' homes if necessary. Use means communication like cellphone more make it easier public For get information Which required. Obstacle Which faced officer instructor in carry out socialization contraception period long program family planned BKKBN Sidomulyo South Lampung is a lack of human resources (extension workers), and lack of public awareness of the importance of using long-term contraception long.